O papel das organizações intermediárias na promoção da inovação social: um estudo comparativo entre Brasil e Alemanha - Meire Gonçalves dos Reis (2023)
The present dissertation aimed to analyze how two intermediary organizations belonging to a global network of impact entrepreneurs promote social innovation in distinct contexts. The approach adopted consisted of understanding the social innovation perspectives of each organization by investigating their activities, programs, and actions. To achieve this objective, the case study method was used, with the purpose of conducting a comparative descriptive analysis between the two organizations. The results indicate that Impact Hub Berlin presents greater robustness and support mechanisms for promoting social innovations for its members, through specific programs focused on the pillars that make up the organization's core business. On the other hand, Impact Hub Belo Horizonte focuses more on end activities than on intermediation and support activities for members regarding social innovations, and social or impact entrepreneurship is more in demand than innovations. Additionally, it was found that Impact Hub Berlin acts as an intermediary, while Impact Hub Belo Horizonte plays a more supportive role, focusing on external organizations or clients. It was also observed that both organizations presented a partial understanding of the concept and lacked more comprehensive official definitions to guide their actions more effectively. Finally, the recommendations presented emphasize the importance of a clearer and well-defined action strategy, which requires a precise understanding of the concept of social innovation, as well as its application.